THE UTILIZATION OF CONTEXTUAL TEACHING LEARNING TO ENHANCE STUDENTS’ ENGLISH LEARNING OUTCOMES: AN ACTION RESEARCH - Yahfenel Evi Fussalam; Resi Silvia; Elmiati Elmiati; Leni Marlina (Universitas Muhammadiyah Muara Bungo, 2023)
The research on the fifth-grade students of SD Negeri 093 Sungai Abang Village was driven by the researchers’ desire to enhance students' learning outcomes, especially in the subject of English. The researcher's findings indicated that the average student achievement scores were still low, below the Minimum Mastery Criteria (KKM) set by the school. Out of a total of 12 students, only 2 students or 16.7% reached the KKM. As an alternative solution to this issue, the researcher conducted Classroom Action Research (CAR) by implementing the Contextual Teaching and Learning (CTL) method. The research was conducted in the second semester of the 2022/2023 academic year, involving 12 students. The data analysis results from Cycle I showed that the average class score had reached the KKM, with 9 out of 12 students (75%) reaching the KKM. Students' learning outcomes improved in Cycle II, where almost all students, 11 out of 12 (91.7%), reached the KKM. This research demonstrates that the use of CTL was appropriately applied in English language learning, particularly in the material taught in the higher grade levels as the subject of the research.